Restoration of adaptive cardioprotection impaired by metabolic syndrome in rats by the PPARα activation - N. V. Naryzhnaya; I. A. Derkachev; B. K. Kurbatov; M. A. Sirotina; M. Kilin; L. N. Maslov (Acta Biomedica Scientifica, 2024)
Background. It is known that the protective effect of adaptation and conditioning influence is weakened in animals with metabolic syndrome. Metabolic syndrome may be the basis for the failure of cardioprotection in clinical settings.The aim of the study. To identify the relationship between disorder in carbohydrate and lipid metabolism and a decrease in the effectiveness of the infarct-limiting effect of moderate chronic normobaric hypoxia; to check the possibility of correcting reduced cardioprotection by normalizing carbohydrate and lipid metabolism.Methods. The  study included 64  Wistar rats. Metabolic syndrome was  induced by feeding animals a high-carbohydrate, high-fat diet for 84 days. Chronic normobaric hypoxia was carried out for 21 days in the following mode: 12 % O2 : 0.3 % CO2. Metformin at  a  dose of  200  mg/kg/day or  PPARα agonist WY14643 at  a  dose of 1 mg/kg/day were added to the drinking water of rats with metabolic syndrome during adaptation period to hypoxia. A 45-minute coronary occlusion and 120-minute reperfusion were performed, and the infarct size was determined. Indicators of lipid and carbohydrate metabolism, leptin, and adiponectin were studied in the blood serum.Results. The infarct-limiting effect of chronic normobaric hypoxia was weakened in animals with metabolic syndrome. Infarct size showed a direct correlation with decreased glucose tolerance and serum triglyceride levels. Using metformin therapy did not lead to the restoration of the infarct-limiting effect of chronic normobaric hypoxia, while the  normalization of  lipid metabolism with the  use of  the  PPARα agonist WY14643 corrected the  impairment of  adaptive cardioprotection in  rats with metabolic syndrome.Conclusion. The  lack of  cardioprotection at  chronic normobaric hypoxia in  rats with  metabolic syndrome is  associated with  impaired carbohydrate and  lipid metabolism. The PPARα agonist restores impaired lipid metabolism and adaptive cardioprotection.